Effects of different imidazole accelerators on curing behavior and cross‐linked network of epoxy resin/phenolic resin/benzoxazine ternary system. (28th October 2021) - Gou, Haolan; Zhao, Yingying; Zhou, Yanglong; Wei, Wei; Fei, Xiaoma; Li, Xiaojie; Liu, Xiaoya
Abstract: For the molding compounds used in electronic packaging, curing accelerators play a significant effect on the curing behavior of thermosetting resins, thus the cross‐linked structure and performance of the cured product. In this study, nine commercially available imidazole compounds, divided into three types, were introduced into a polyfunctional epoxy resin (E1 )/XYLOK phenolic resin (P1 )/MDA benzoxazine (B1 ) ternary system to reduce the curing temperature for molding processing. To understand the cross‐linked structure of the cured product, the ternary system was divided into unitary system and binary system, and the curing behavior and chemical structure of each system was monitored by differential scanning calorimetry and Fourier transform‐infrared systematically. Due to the nucleophilicity of tertiary amines influenced by the steric hindrance effect, it was discovered that the reaction activity of epoxy resin initiated by nine imidazole compounds, was significantly different. However, the ring opening of benzoxazine occurs at a high temperature, even catalyzed with imidazoles, and its curing behavior was nearly the same owing to the unique ring‐opening mechanism initiated by active hydrogen of imidazole. In addition, phenolic resin elevates reaction activity for both epoxy resin and benzoxazine. The cross‐linked structure of E1 P1 B1 ternary system was proposed based on the experimental results from each system. It suggested that the formed network of the E1 P1 B1 cured product with Type I and II imidazoles is mainly IPN structure, while the cured products of E1 P1 B1  + Type III is the copolymerization of epoxy, phenolic and benzoxazine. This paper systematically illustrated the ideal chemical structures of epoxy resin/phenolic resin/benzoxazine ternary system with different imidazole compounds, which is valuable for industrial application of resin‐based materials.